G373(P) Ventilator associated pneumonia in paediatric intensive care (picu). (May 2019) - Riddick, LJ; Hemingway, J; Lumsden, J
Abstract : Background: Ventilator associated pneumonia (VAP) is the second highest hospital acquired infection(HAI) in Paediatric Intensive Care and effects 12% of all ventilated patients, with a rate of 3 per 1000 ventilated days (1). Risk factors for developing VAP include prolonged time on ventilator, poor gastric protection and oral hygiene (2). Local PICU guidance provides an algorithm to identify, treat and monitor VAP. A local audit was undertaken to review incidence and management of VAP on our PICU. Method: The data was collected from screening tools as per the VAP evaluation algorithm in PICU. Potential patients were identified from daily adverse event information collected for the SANDWICH (Sedation and Weaning) Trial. There were 9 possible cases collected from a patient cohort of 339 patients (284 ventilated), accumulating 1510 ventilated days over the 6-month data collection. This equated to 6 days on average per ventilated patient. 2 were excluded due to not meeting VAP diagnostic criteria. Two additional patients were identified using a Safety Huddle tool. Local guidelines were reviewed for the diagnosis of and risk factors for VAP as well as collected data for the Clinical Pulmonary Infection Score (CPIS) to determine the severity. Result: From the 9 patients with confirmed VAP (CXR changes, ventilated more than 48 hours and one other CDC criteria, there was a total of 340 days with an average time of 37.8 days ventilated (range 6–74 days) amongst this cohort. The mean time of developing VAP was 16.4 days, with a rate of 5.9 per 1000 ventilated days. Overall patients were treated for a mean of 6 days. Of the 9 patients, 7 had positive sputum culture results, 5 of which had sensitivities reported, for which antibiotic changes were made. Conclusion: Data collection highlighted the difficulties in identifying VAP accurately as well as the limitations in documentation for CPIS and risk factors. CPIS is not an accurate score in paediatric patients, limited by the need for numerous investigations and invasive procedures. Safety Huddle documentation has proven valuable in the identification of VAP. An improvement to screening and monitoring of VAP in PICU would include a paediatric orientated risk and severity score, which is standardised nationally.